Acute Kidney Injury Following Ingestion of Averrhoa bilimbi Juice - Billah, Md Mostarshid; Rahman, Md Anisur; Rahim, Muhammad Abdur; Swarna, Ayesha Tabassum; Mitra, Palash; Chowdhury, Tufayel Ahmed; Ananna, Mehruba Alam; Samad, Tabassum; Haque, Wasim Md Mohosinul; Iqbal, Sarwar; et al. (Bangladesh Critical Care Journal, 2015)
Bilimbi/belembu fruit belongs to the family of Oxalidacae, species Averrhoa bilimbi. Freshly prepared concentrated juice of bilimbi has very high oxalic acid content and consumption carries a high risk of developing acute kidney injury (AKI) by deposition of calcium oxalate crystals in renal tubules. AKI due to Averrhoa bilimbi juice injestion is very rare. We report the case history of a 60-year-old hypertensive, dyslipidemic patient, with normal renal function, who ingested around 600ml of juice in fasting state for treating dyslipidemia. The patient developed AKI and required three sessions of hemodialysis. Her renal function returned to normal after five weeks. Bangladesh Crit Care J September 2015; 3 (2): 71-73